Open-Ended Problems Improve High-Level Thinking Skills of Vocational High School Students with CPS Learning - Arina Ulil Faroh; Amin Suyitno; Zaenuri Zaenuri (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2022)
Higher Order Thinking Skills (HOTS) are abilities that consist of analyzing, discovering, and creating. HOTS is an ability that students must have to solve various problems. However, not all students have high HOTS, so efforts are needed to increase students' HOTS. The purpose of this article is to determine the effect of open problems on increasing students' HOTS in trigonometry material. The subjects of this research were 26 students of class X SMK. The research method used is a mixed method, which combines qualitative and quantitative methods. The research instrument used is the test results, the test used has been tested for validity. Quantitative data analysis used paired t-test, while qualitative data analysis used data reduction, data presentation, data interpretation, and drawing conclusions/leverages. after learning by applying the Creative Problem-Solving (CPS) model, students work on questions in the form of open problems. The results obtained are: (1) there is a significant increase in the value indicated by the value of Sig. 0.00 < 0.05 it also shows that the provision of open-ended problems during CPS learning able to increase students' HOTS. (2) students with high HOTS can apply the HOTS cognitive domain well, while students with moderate and low HOTS have difficulty applying the HOTS cognitive domain. the provision of open problems and appropriate learning models can increase students' HOTS.